Creating change through social entrepreneurship: the case of girls’ school dropouts in Uganda - Nsereko Isa; Bignotti Alex; Farhoud Mohamed (Emerald, 2022)
Subject area
This case focusses on social innovation and social entrepreneurship in Africa, specifically looking at behavioural characteristics of social entrepreneurs, their motivations to create social value and the application of personal initiative theory. The case discusses the self-starting proactiveness and innovation traits of the social entrepreneur. The social business model canvas will be used to analyse the social enterprise’s business model.
Study level/applicability
Students of social entrepreneurship, development studies, sustainable livelihoods and asset-based development. It is useful for customised or short programmes on social entrepreneurship or for students with a background in business wanting to understand social enterprise as a vehicle for social and economic change. As such, this case is written for Business Management and Entrepreneurship undergraduates or students of elective courses in social entrepreneurship (“understanding” and “remembering” learning activities under Bloom’s taxonomy). When personal initiative theory is used, the case provides an initial understanding of social entrepreneurship in a less developed context for post-graduate students and may be used for higher-order learning activities (“analysing” and “applying”).
Case overview
The case tells the story of Dr Engr Moses Musaazi, who is a Social Entrepreneur and Managing Director of Technology for Tomorrow (T4T). Troubled with the persistent social problems in his country. Musaazi, through T4T, strived for social innovations to reduce school dropouts of Ugandan girls. While exploring Moses’ journey for solving persistent social problems through social innovations, students will be able to understand, remember, analyse and apply Dees’ (2001) social entrepreneurial behaviours and Santos’ (2012) theory of social entrepreneurship. The case discusses what motivates African social entrepreneurs to start a social venture (Ghalwash, Tolba, & Ismail, 2017). Students will apply personal initiative theory to identify the social entrepreneurial behaviours displayed in the creation of social ventures. To exemplify and analyse the different components of social ventures’ business model, the social business model canvas by Sparviero (2019) will be introduced.
Expected learning outcomes
The teaching objectives are Objective 1. Students are able to remember, understand, identify and apply the social entrepreneurial behaviours as defined by Dees (2001) and the elements of Santos’ (2012) theory of social entrepreneurship to Dr Moses Musaazi’s case as a social entrepreneur. Objective 2. Students remember, understand and identify what motivates social entrepreneurs in less developed economies to create social value (Ghalwash et al., 2017). Objective 3. Early-stage postgraduate students are able to apply and analyse (also evaluate and create for higher-level post-graduates) personal initiative theory to explain the emergence of social entrepreneurial behaviour and especially how innovation, self-starting and proactiveness may lead to social entrepreneurial venture start-up (Frese, Kring, Soose, & Zempel, 1996). Objective 4. Students use the social business model canvas (Sparviero, 2019) as a tool to understand, analyse and improve a social-enterprise business model.
Supplementary materials
Supplementary learning materials are provided in the Teaching Note (Table 1). Table1, which includes videos and their description. Also, a link to Uganda’s sustainable development index is provided (the focus is sustainable development goals [SDGs] 3: Good health and well-being, SDG 4: Quality Education, SDG 5: Gender equality, SDG 10: Reduced inequalities).